2017
DOI: 10.1128/aem.01660-17
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and Phenotypic Characteristics Associated with Biofilm Formation by Human Clinical Escherichia coli Isolates of Different Pathotypes

Abstract: Bacterial biofilm formation is a widespread phenomenon and a complex process requiring a set of genes facilitating the initial adhesion, maturation, and production of the extracellular polymeric matrix and subsequent dispersal of bacteria. Most studies on biofilm formation have investigated nonpathogenic K-12 strains. Due to the extensive focus on laboratory strains in most studies, there is poor information regarding biofilm formation by pathogenic isolates. In this study, we genotypically and phenotypically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 91 publications
(99 reference statements)
2
51
0
1
Order By: Relevance
“…Previous studies have shown variations in the ability of different E. coli strains to produce biofilm under conditions relevant for the food production chain [14,15]. E. coli strains also display variations in biofilm matrix composition which can be visualized when grown on agar plates with Congo Red and Coomassie Blue dyes (CR agar plates) [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown variations in the ability of different E. coli strains to produce biofilm under conditions relevant for the food production chain [14,15]. E. coli strains also display variations in biofilm matrix composition which can be visualized when grown on agar plates with Congo Red and Coomassie Blue dyes (CR agar plates) [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…We studied and optimised biofilm formation on different surfaces and under different growth conditions. Biofilm formation differs in different E. coli strains, shown both in the literature (for example, (Schiebel et al 2017)) and in this study, therefore, such studies on different strains are important. In addition, many studies focus on pathogenic E. coli strains, thus studies on non-pathogenic strains offer an interesting comparison.…”
mentioning
confidence: 54%
“…The curli genes occur in most commensal as well as human and animal pathogenic E. coli isolates and Salmonella enterica serovars [73] , [74] . However, although the csg genes are present, their expression pattern can vary considerably depending on the lifestyle of the bacterium or the infection site, even within a species.…”
Section: Curlimentioning
confidence: 99%
“…However, although the csg genes are present, their expression pattern can vary considerably depending on the lifestyle of the bacterium or the infection site, even within a species. While curli were originally thought to be expressed mainly at ambient temperatures [8] , [75] , it now seems that depending on the growth medium, commensal E. coli as well as enteropathogenic E. coli , enterotoxigenic E. coli , uropathogenic E. coli (UPEC), enteroaggregative E. coli , avian pathogenic E. coli and E. coli isolates causing sepsis can express curli at 37 °C [74] , [76] , [77] , [78] , [79] , [80] . Strikingly, in enteroinvasive E. coli , Shigella spp.…”
Section: Curlimentioning
confidence: 99%